2019
DOI: 10.1002/iub.2222
|View full text |Cite
|
Sign up to set email alerts
|

The role of miR‐146a in viral infection

Abstract: Cellular microRNAs (miRNAs) were identified as a key player in the posttranscriptional regulation of cellular‐genes regulatory pathways. They also emerged as a significant regulator of the immune response. In particular, miR‐146a acts as an importance modulator of function and differentiation cells of the innate and adaptive immunity. It has been associated with disorder including cancer and viral infections. Given its significance in the regulation of key cellular processes, it is not surprising which virus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 146 publications
(325 reference statements)
1
36
0
Order By: Relevance
“…In addition, overexpression of hsa-miR-146a leads to decreased phosphorylation of NF-кB during infection [ 24 ]. The conclusions were similar to another finding which demonstrated that increased expression of hsa-miR-146a enhanced DENV replication by targeting the TRAF6-mediated NF-кB pathway [ 49 ]. These results suggested a role of hsa-miR-146a-mediated targeting of the NF-кB pathway during CHIKV pathogenesis.…”
Section: Role Of Mirnas During Chikv Infectionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, overexpression of hsa-miR-146a leads to decreased phosphorylation of NF-кB during infection [ 24 ]. The conclusions were similar to another finding which demonstrated that increased expression of hsa-miR-146a enhanced DENV replication by targeting the TRAF6-mediated NF-кB pathway [ 49 ]. These results suggested a role of hsa-miR-146a-mediated targeting of the NF-кB pathway during CHIKV pathogenesis.…”
Section: Role Of Mirnas During Chikv Infectionsupporting
confidence: 90%
“…Many reports have suggested that joint inflammation is associated with arthritic-like symptoms during CHIKV infection [ 147 ]. hsa-miR-146 has been associated with many viral and microbial infections and also with inflammatory conditions such as RA [ 49 , 148 , 149 ]. An upregulated expression of hsa-miR-146a was observed in synovial fibroblasts during CHIKV infection [ 24 ].…”
Section: Possible Role Of Mirnas In Bone Homeostasis In the Contexmentioning
confidence: 99%
“…These molecules exert their effects via targeting a variety of molecular and cellular mechanisms [148][149][150][151][152]. Hence, miRNAs could be used as diagnostic, prognostic and therapeutic biomarkers in the treatment of different diseases such as stroke, cancer, cardiovascular diseases, infection diseases, diabetes, and viral infections [153][154][155][156][157][158][159][160][161][162][163].…”
Section: Micrornasmentioning
confidence: 99%
“…Considering the increased level of STAT1 and other targets of miR-146a in the lungs of patients infected with SARS-CoV-2, miR-146a can be decreased in SARS-CoV-2 infection. The preventive role of STAT1 against SARS-CoV replication has been previously reported [ 43 ]. In order to retaliate, SARS-CoV encodes a STAT1 antagonist (ORF6) to escape from eradication [ 44 ].…”
Section: Discussionmentioning
confidence: 97%
“…MiR-146a is predicted to target 21 up-regulated genes in SARS-CoV-2 infection. The increased level of miR-146a in a wide range of viral infections including HCV, HBV, influenza A, HIV, H1N1, H3N2, and EBV has been previously reported [ 43 ]. miR-146a protects the virus against the host through targeting and inhibiting STAT1 protein.…”
Section: Discussionmentioning
confidence: 98%